Potential of Deploying Empty Fruit Bunch (EFB) for Biomass Cofiring in Malaysia's Largest Coal Power Plant - Salleh S.F.; Abd Rahman A.; Abdullah T.A.R.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomass; Coal; Energy policy; Fruits; Palm oil; Pelletizing; Biomass cofiring; Coal power plants; Empty fruit bunches; Low-carbon electricities; Palm oil mills; Fossil fuel power plants